2018
DOI: 10.1161/circulationaha.118.034986
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Hospitalization for Heart Failure and Case-Fatality Among 3.25 Million People With and Without Diabetes Mellitus

Abstract: -Recent clinical trials of new glucose-lowering treatments have drawn attention to the importance of hospitalisation for heart failure as a complication of diabetes. However, the epidemiology is not well described, particularly for type 1 diabetes. We examined the incidence and case-fatality of heart failure hospitalisations in the entire population aged 30 and older resident in Scotland during 2004 to 2013. -Date and type of diabetes diagnosis were linked to heart failure hospitalisations and deaths using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
115
0
8

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 21 publications
4
115
0
8
Order By: Relevance
“…In patients with diabetes, hyperglycemia leads to endothelial dysfunction, resulting in low-grade in ammatory, prothrombotic, proliferative, and vasoconstrictive processes [28]. These mechanisms may converge and lead to hypertension, atherosclerotic cardiovascular disease, and heart failure [2,3,[29][30][31]. Hypertension may be worsened in a cold environment [5,[32][33][34][35][36], elevating the myocardial workload and myocardial oxygen demand, or exacerbating functional valve insu ciencies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In patients with diabetes, hyperglycemia leads to endothelial dysfunction, resulting in low-grade in ammatory, prothrombotic, proliferative, and vasoconstrictive processes [28]. These mechanisms may converge and lead to hypertension, atherosclerotic cardiovascular disease, and heart failure [2,3,[29][30][31]. Hypertension may be worsened in a cold environment [5,[32][33][34][35][36], elevating the myocardial workload and myocardial oxygen demand, or exacerbating functional valve insu ciencies.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is a complex metabolic disease that can affect vital functions [1]. Cardiovascular complications, such as atherosclerotic cardiovascular and heart failure, are the leading cause of morbidity and mortality in patients with type 2 diabetes mellitus (T2DM), which is the most common form of the disease [2][3][4]. Treatment of cardiovascular comorbidities comprises drug therapy; however, progression and/or exacerbation of these diabetes-related circulatory complications often require surgical intervention.…”
Section: Introductionmentioning
confidence: 99%
“…In 2017, 16% (N ≈ 111,000) of cardiovascular (CV)-related deaths were estimated to be attributable to T2DM [3]. Individuals with T2DM are also at increased risk of hospitalization due to heart failure (HF) [4,5]. In the United States, about one-third of adults with diagnosed diabetes also had CKD (stages 1-4) [6].…”
Section: History Of Conditionmentioning
confidence: 99%
“…An epidemiological study revealed that the incidence of HF is approximately 2 times higher in patients with diabetes than patients without diabetes [4]. Clinically, hypertension and coronary heart disease are well known causes of HF.…”
Section: Introductionmentioning
confidence: 99%